Tinjauan Yuridis Penegakan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Perundungan Menurut UU No. 11 Tahun 2012 Tentang Sistem Peradilan Anak Dan Hukum Islam (Studi Kasus di Polresta Banda Aceh) - Maulana Fickry Albaba; Sulfanwandi; Faisal Yahya (Program Studi Hukum Pidana Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The phenomenon of bullying, especially by children, occurs every year in Banda Aceh City and has a significant negative impact on both victims, perpetrators, and the surrounding environment. This issue requires an approach that is not only oriented towards justice for victims, but also on protecting the rights of children as perpetrators. By paying attention to the balance between justice for victims and protection for perpetrators, while supporting the main objective of the SPPA Law to guarantee the best interests of children. This research was conducted at the Banda Aceh Police as the location for the case study research. This study aims to determine the legal review of law enforcement against children as perpetrators of bullying crimes according to Law no. 11 of 2012 concerning the juvenile justice system and Islamic law, law enforcement efforts against children as perpetrators of bullying crimes at the Banda Aceh Police, and inhibiting factors in law enforcement against children as perpetrators of bullying crimes at the Banda Aceh Police. The research method used is a qualitative method with an empirical legal approach through interviews, literature studies, and documentation. The results of the study indicate that law enforcement against children as perpetrators of bullying in Banda Aceh City refers to the principle of restorative justice as regulated in the Juvenile Justice System Law. This approach prioritizes diversion rather than criminal punishment. However, there are several obstacles, such as minimal public awareness and lack of coordination between related parties in handling cases. From the perspective of Islamic Law, an educational approach and moral improvement are prioritized to prevent bullying behavior and improve the behavior of children as perpetrators.